Association of Glycemic Control With Different Diets Followed by Patients With Type 2 Diabetes: Findings From Qatar Biobank Data - Tayyem, Reema; Hamdan, Aya; Alhmmadi, Karmen; Eissa, Yasmin; Al-Adwi, Maryam; Al-Haswsa, Zinab; Bawadi, Hiba; Shi, Zumin (Frontiers in Nutrition, 2022)
Background: Diabetes mellitus type 2 (T2DM) is one of the most common diseases worldwide. Unhealthy dietary habits may lead to T2DM, which is also influenced by the extent of education and knowledge of appropriate diets for this disease. Aim: The aim of this study is to highlight the possible association between following different types of diet (low-fat diet, low-calorie diet, low-salt diet, and more than one diet) and glycemic control among Qatari and long-term resident patients with T2DM. Methods: This study is a secondary data analysis. Qatar Biobank (QBB) data on 2448 T2DM patients aged 18-60 years was obtained. The first group included participants with HbA1C<7%, while the second included those with HbA1c≥7%. Results: The results of the association of glycemic control with different diets followed by patients with type 2 diabetes were adjusted in four models. In the 4th model (adjusted for gender, age, sociodemographic, anthropometric, dietary habits, comorbidities and medications), results showed that poor patients with poor glycemic control have higher odds (OR 1.90; CI (1.00-3.63)) of following a low-salt diet. The same observation was found in the low-fat diet (OR 1.73; CI (1.06-3.07)). However, patients following more than one diet showed lower odds of having poor glycemic control for about 32% (OR 0.69; CI (0.48-0.98)). Not modifying the diet increased the risk of having HbA1C level significantly≥7% for about 16% (OR 1.16; CI (1.07-1.43)). Conclusion: Diet and lifestyle are vital factors that can affect HbA1C levels. The findings of this secondary analysis showed that better glycemic control of the patients was observed in patients following more than diet from the studied diets.